Applicability of Sudoku game for building the cognitive model of a student for career assessment - an analytical study - Chandra Prakash, V.; Sastry, J. K. R.; Anusha, K.B.; Spandana, A.B.; Dhatrija, N.; Nikhil, V. (International Journal of Engineering and Technology, 2017)
Career assessmentÂ helps a student understand how a variety of personal attributes (i.e., academic record, aptitudes, skills, preferences, motivations, etc.) impact his/her successful professional career and satisfaction. The professional life of a student is very much dependent on the initial choice of the career that the student would like to pursue. Nowadays, during job recruitment process, a student is assessed based on IQ tests, Verbal tests, Reasoning tests, etc. Every student has some psychological factors (i.e., decision-making, patience & perseverance, logical thinking, learning ability, etc.) that are not considered during these tests. As a result, some students may not lead successful careers in future. There are a very few ways to assess those psychological factors of a student and one such way is through Game playing. Through an analytical study, it was found that "Sudoku" is the best game to assess psychological factors, especially decision-making power, of a student. The authors proposed an Expert system that conducts Sudoku game for a student, assesses various psychological factors, builds a cognitive model of the student and provides career assessment.